Carthamin yellow attenuates brain injury in a neonatal rat model of ischemic–hypoxic encephalopathy by inhibiting neuronal ferroptosis in the hippocampus - Zhou Yuanyu; Wang Yuebin; Wu Xiaoqing; Wu Junjie; Yan Jianhui; Su Wei (Translational Neuroscience, 2023)
Hypoxic–ischemic encephalopathy (HIE) is a common neurological disorder characterized by ischemia and hypoxia in the perinatal period, which seriously affects the growth and development of newborns. To date, there is no specific drug for the treatment of HIE. Previous studies have shown that ferroptosis plays an important role in the pathogenesis of HIE. Carthamin yellow (CY) is believed to have antioxidant and anti-inflammatory effects. However, no studies have reported the role of CY in ferroptosis in HIE in vivo until now. The aim of this study was to investigate the effect and mechanism of CY on HIE in vivo and to provide an experimental basis for the clinical treatment of HIE. The results demonstrated that CY increased the expression of NeuN in the neonatal rat hypoxic-ischemic brain damage (HIBD) model. Further exploration revealed that CY increased the expression of glutathione peroxidase 4 and ferritin heavy chain 1 while it decreased the expression of PTGS2 and ACSL2. Moreover, CY decreased malondialdehyde expression and increased superoxide dismutase and glutathione expression in vivo. The findings also indicated that CY downregulated the expression of Nrf2 and Keap-1. In conclusion, this study demonstrated that CY attenuated brain injury in an experimental HIBD model, potentially by alleviating hippocampal neuronal ferroptosis through inhibition of the Nrf2/Keap-1 signaling pathway. These findings provide a novel therapeutic strategy for the clinical treatment of HIE.